Fatty Acid Profiling And Determination of Nutritional Quality of Lipids In Selected Commonly Consumed Fishes In Dhaka City - Miah, Shakil; Akhter, Kazi Turjaun; Akter, Sumya; Sadiq, Zafar As; Jahan, Israt; Bhuiyan, Nizamul Hoque; Kabir, Alamgir; Jaiswal, Sanni; Saha, Susmita; Ahmed, Eyad (Bioresearch Communications, 2024)
Background: Fish is one of the most widely consumed foods worldwide and It has been the third most-consumed food item in Bangladesh. Objective: This study thoroughly analyzed the fatty acid content and nutritional quality of lipids extracted from five widely consumed fish species in Dhaka city, since fish fatty acid profile is an essential indicator of fish lipid quality. Methodology: Five commonly consumed fishes, which were analyzed in the current study, were Labeo bata, Wallago attu, Chanda nama, Labeo calbasu, and Channa striata. The crude lipid content was assessed using Folch method and fatty acid profiles were assessed by Gas chromatography method. The fatty acid profile data were then used to calculate various nutritional indices to assess the overall quality of the fish lipids. Results: Four of the fishes named L. bata, W. attu, C. nama, and C. striata, were classified as lean or low-fat fish based on their extracted fat percentages falling below 4%. In contrast, L. calbasu stood out as a medium-fat fish with a fat content of 4.01 ± 0.26%. A total of 32 distinct fatty acids were obtained in the study. The analysis of the fatty acid profiles revealed a substantial amount of saturated fatty acids, making up around 40% of the total fatty acids. Palmitic acid was identified as the most predominant saturated fatty acid. Monounsaturated fatty acids constituted 25-40% of the total fatty acids, with oleic acid recognized as the predominant monounsaturated fatty acid. The fish samples were found to have substantial amounts of nutritionally advantageous polyunsaturated fatty acids (PUFAs), with omega-3 fatty acids comprising up to 18%. The ratio of ω-3 to ω-6 ranged from 0.4 to 2.0 across the different fish species. Higher values for desirable fatty acids are preferable, and the fish had a 52-70% desirable fatty acids range. Conversely, lower values for hypercholesterolemic fatty acids are preferred, and the fish had a range of 24.6-30.9%. The Atherogenecity index (AI) and Thrombogenecity index (TI) of the samples ranged from 0.44-0.88 and 0.43-0.61, respectively. The comprehensive analysis of fatty acids and assessment of lipid quality provide valuable information regarding the nutritional importance of consuming these locally available fish species as part of a healthy diet in Bangladesh. Conclusion: In summary, the assessment of the indices indicates that the lipids found in L. calbasu have a comparatively more advantageous nutritional composition when compared to other species that were studied. Nevertheless, all fish species offer a harmonious combination of beneficial fatty acids and specific less favorable components regarding their overall fatty acid composition. Bioresearch Commu. 11(1): 1679-1687, 2025 (January)